KELAPA DALAM BUDAYA BALI SERTA UPAYA PELESTARIANNYA - Nyoman Adiputra; I Nyoman Wardi (Bumi Lestari Journal of Environment, 2015)
The coconut has a meaningful role in Balinese live. Economically, the coconut is becomingone of the commodity of Bali. The coconut products such as young and old leaves, flower,young and old fruits and the coconut stems, all of them used by the Balinese. Coconut isconsidered as food stuff, building materials, and for handycrafts. This article reports thecultural classification of coconut, based on Balinese way of looking. At least there are 12kinds of coconut, namely: 1) nyuh bulan, 2) nyuh udang, 3) nyuh gading, 4) nyuh gadang, 5)nyuh sudamala, 6) nyuh bojog, 7) nyuh surya, 8) nyuh rangda, 9) nyuh be julit, 10) nyuhbongol, 11) nyuh mulung, and 12) nyuh harum. The intended coconuts are used mainly forreligious ceremony. The aim of this article is to desiminate the intended information for it’sconservation and preservation. By knowing that, as a Balinese, hopefully, that every bodyfully concerned in the preservation program of coconut until forever.